African Traditions that Enhance Philosophical Ideologies: A Review of Yusef Waghid’s African Philosophy of Education Reconsidered: On Being Human (London: Routledge, 2014, pp. 168) - Chabilall, Jyothi (South African Journal of Higher Education, 2016)
Yusef Waghid’s book makes a case for an African philosophy of education to develop in a rational, principled and stimulating context in order to ultimately produce realistic solutions to African problems. The book addresses the paucity of conversations in respect of a particular African philosophy of education that integrates reasonableness, culture and emotion, including the empowerment of African women to address cultural and societal marginalization, as part of African philosophy of education. Firstly, the review article espouses my point that an African philosophy of education discourse is meant to move beyond a mere discussion of culture and tradition to being an innovative, scientific practice aimed at resolving dilemmas on the African continent. The book uses ubuntu as an instance of African philosophy of education to do pragmatist work in resolving educational and societal problems on the continent in relation to justice including equality for all. Secondly, I am mindful of Waghid’s assertion that an African philosophy of education necessitates rational debate to achieve a coherent understanding of the manner in which age old traditional thoughts may be incorporated into an innovative African ethos. Ultimately, Waghid advocates that teaching and learning should provoke attitudes of openness and criticality but also caring to encourage those who guide to be aware of student diversity as acknowledged by African philosophers.